EFFECT OF MICROSPHERE SIZE AND FORMULATION FACTORS ON DRUG RELEASE FROM CONTROLLED-RELEASE FUROSEMIDE MICROSPHERES - (:unkn) unknown (MARCEL DEKKER INC, 1991)
Controlled-release furosemide microspheres were prepared with various combinations of Eudragit L: Eudragit RS and Eudragit S: Eudragit RS and release of drug from microspheres containing these polymers in different ratios was studied. A wide range of release rates of drug can obtained by a simple change in the ratio of polymers. An increase in Eudragit RS content of polymer microsphere matrix brought about a decrease in the release rate. On the other hand, the effect of particle size on the drug release rate from furosemide microspheres was also investigated. The effect of microsphere sizes on release rate depends on the type of Eudragit. The decrease in release rates of small microspheres may be due to agglomerate formation. Dissolution data indicated that the release followed Higuchi's matrix model kinetics.
Keywords: POLYCAPROLACTONE